PERANCANGAN SISTEM PENJUALAN BARANG DAN JASA UNTUK TOKO INTIKARYA ALUMINIUM - Dedofin Dedofin; Bagus Mulyawan (Fakultas Teknologi Informasi Universitas Tarumanagara, 2018)
System Application Sales of Goods and Services for Stores Intikarya Aluminum is a system application sales are made in order to facilitate the transaction process Intikarya store Aluminum with a desktop-based application, web and mobile. This application is made using the programming language C # and Java with .NET and ASP.NET framework. Method of application design using the System Development Life Cycle. Results Testing was conducted by usig Blackbox and User Acceptance Test. With this application transactions conducted at Store Intikarya Aluminum becomes easier. The system made also implements Linear regression methods were used to predict the stock for the next month.